Salvia miltiorrhiza Bunge (Danshen) and Bioactive Compound Tanshinone IIA Alleviates Cisplatin-Induced Acute Kidney Injury Through Regulating PXR/NF-κB Signaling - Dou, Jing-Yun; Zhang, Min; Cen, Huan; Chen, Yi-Qin; Wu, Yi-Fan; Lu, Fuhua; Zhou, Jiuyao; Liu, Xu-Sheng; Gu, Yue-Yu (Frontiers in Pharmacology, 2022)
Graphical Abstract